Meteorological Study of Foehn Phenomena in Guilan Province - Abbas Ranjbar Saadatabadi; Jamileh Pourmirza (جغرافیا و توسعه, 2015)
Foehn phenomenon is one of Mesoscale phenomenon in which large scale patterns of pressure fields have a great and important role in its creation and control. In northern  part of the country, the condition is ready for occurrence of such events and remains a considerable effects. This phenomenon is typically associated with intense warm and dry winds which considerably increases temperature, decrease of relative humidity , drop and change of other meteorological parameters and has different consequences including firing the forests and meadows in these areas. In this study, by using meteorological data and maps during 2000-2008 for  , fohen parameter was investigated forr  Rasht, Anzali and Astara stations. The results showed that this phenomenon occurred in cold months and has the most frequency in the months of December and January . From spatial distribution view, Rasht has the most frequency and intensity, in all the studied cases, settlement of high pressure system in south part of Alborz and low pressure system in southern part of Mazandaran sea (Caspian sea) are the main factors of Foehn occurrence  in Guilan. These conditions is accompanied respectively with cold height ridge and warm height trough  and low levels of troposphere. Pressure horizontal gradient between two low and high pressure systems force the mountainous cold air to the north part which due to cold air heaviness and after passing the mountain chains, descends and by moving to lower heights , while being warm , it will accelerate. Mechanism of this phenomenon occurrence in Guilan Province has a unique characteristics, so that settlement of cold air on Alborz heights and its southern parts together with pressure gradient between southern and northern areas  of Alborz and the presence of Sefidroud Valley has caused Foehn phenomenon mechanism in Guilan to be a combination of air settlement  and gap wind.